2017
DOI: 10.1097/jpn.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Global Zika Epidemic Locally

Abstract: Escalating evidence for the fetal impact of Zika virus infection required a change in care by all prenatal providers. This article describes an effective model of rapid implementation of universal prenatal screening at one hospital and its network of community health centers for a large and diverse immigrant population exploring the challenges, experiences, and lessons learned. Implementation of national recommendations required a workflow change, challenging a system with a heterogeneity of settings and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…10 Another study showed that the use of a clinician champion was key to the success of universal screening for Zika virus during prenatal visits. 11 With respect to social needs screening, implementation was more likely to be successful if an internal advocate was present 12 to facilitate the process of incorporating screening into clinical routines; however, in this study, the screening advocate was usually not a clinician. To our knowledge, no other studies examine the impact of clinician champions on social needs screening.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…10 Another study showed that the use of a clinician champion was key to the success of universal screening for Zika virus during prenatal visits. 11 With respect to social needs screening, implementation was more likely to be successful if an internal advocate was present 12 to facilitate the process of incorporating screening into clinical routines; however, in this study, the screening advocate was usually not a clinician. To our knowledge, no other studies examine the impact of clinician champions on social needs screening.…”
Section: Introductionmentioning
confidence: 84%
“…Other studies have shown that screening can be highly successful during a pandemic with the active participation of clinician champions. 11 The higher screening rates during the pandemic may be attributed to clinicians recognizing increased social needs among the patient population due to the soaring rates of unemployment, food insecurity, and housing instability reported in the media and during individual encounters. Furthermore, at the peak of the pandemic, clinic visit volumes dropped significantly, leaving clinicians with more time to address the social needs of their patients and families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation